Optimization of Citric Acid Addition on The Effect of Reducing Aflatoxin B1 Levels in Animal Feed - Farida Nuraeni; Tri Aminingsih; Diana Widiastuti; Hesty Nurul Huriyah (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2026)
Aflatoxin B1 contamination in animal feed poses a serious threat to animal and human health, as this compound can cause dangerous toxic effects. The aflatoxin decontamination process in animal feed is a crucial step in maintaining food safety and livestock health. One effective method of aflatoxin decontamination is the use of citric acid, which can reduce aflatoxin contamination without compromising the feed's essential nutrients. Analysis revealed that 9 out of 10 animal feed samples in the Bogor area contained aflatoxin B1 exceeding the European Union's safe limit of 5 µg/kg. The addition of 2N citric acid for 120 minutes was proven to reduce aflatoxin B1 levels by up to 93.45%. Nutritional quality testing showed that the addition of citric acid did not disrupt the essential nutrient content of the feed, as it still met SNI 3148-1:2024 standards. The decontamination method using citric acid has been proven effective in reducing aflatoxin B1 without compromising nutritional quality, thereby improving food safety and supporting livestock health and productivity.